THE IMPLEMENTATION OF BAAMBOOZLE GAME AS AN INTERACTIVE LEARNING MEDIA TO TEACH WRITING OF NARRATIVE TEXT - Eysa Rismandari, Ananda; Ulya, Inayatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Writing is one of the essential productive skills in English learning; however, many students still experience difficulties in organizing ideas, applying grammatical rules, and developing narrative texts effectively. This study aimed to investigate the implementation of Baamboozle Game in teaching narrative writing to the tenth-grade students of SMA Negeri 2 Batang. This research employed a descriptive qualitative design. The participants were students of Class X.2 at SMA Negeri 2 Batang. The data were collected through classroom observation, interviews, questionnaires, and writing tests. The collected data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, conclusion drawing and verification, supported by data interpretation and triangulation to ensure the trustworthiness of the findings. The findings revealed that the implementation of Baamboozle Game created a more interactive and engaging learning environment. Students showed positive responses toward the use of Baamboozle, as it increased their motivation, classroom participation, collaboration, and confidence during the learning process. The writing test results also indicated that most students were able to produce narrative texts with appropriate generic structures, relevant content, logical organization, suitable vocabulary, and acceptable grammar and mechanics. Although several students still experienced difficulties in grammar and internet connectivity during the activities, these challenges did not significantly affect the learning process. In conclusion, Baamboozle Game can be considered an effective and interactive learning medium to support the teaching of narrative writing and to encourage students' active participation in English classrooms.